Unveiling the Antimicrobial of Lactic Acid Bacteria from Gatot Cassava Against Escherichia coli and Salmonella typhi - Dewi Chusniasih; Nadia Alfauzia; Erma Suryanti; Khaerunissa Anbar Istiadi (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Lactic Acid Bacteria (LAB) as probiotics provide many benefits to the body, including suppressing the growth of pathogens in the digestive tract. Antibacterial compounds from LAB can inhibit the presence of pathogenic bacteria. This study aimed to determine the ability of antibacterial compounds from Gatot LAB to inhibit the growth of Escherichia coli and Salmonella typhi bacteria. Methodology: LAB was isolated from cassava gatot, and The LAB isolates obtained were then tested for several LAB characteristics and antibacterial activity against E. coli and S. typhi. LAB characterization based on colony morphology, Gram staining, biochemical testing, coaggregation, and autoaggregation. Findings: There were 7 LAB isolates obtained, namely isolates with codes GNK1, GNK3, GNR2, GNR4, GUR1, GUR3, and GUR5. Isolate GUR3 can inhibit E. coli with the highest inhibition zone of 21.31 ± 3.98 mm. In the antibacterial test against S. typhi, 4 isolates had an inhibitory activity with the highest inhibition diameter by isolate GNK3 of 28.23±3.91 mm. LAB isolates from gatot have the ability to autoaggregate and coaggregate against E. coli and S. typhi. There are 5 isolates that show inhibitory activity against E. coli, namely GNK1, GNK3, GNR2, GNR4, GUR1, and GUR3. Inhibitory activity against S. typhi is shown by 4 LAB isolates, namely GNK1, GNK3, GNR2, and GNR4. Contribution: This research shows that LAB isolates from gatot have potential as probiotic agents with significant antibacterial activity against E. coli and S. typhi, so it can be developed as a natural alternative to control intestinal pathogens.